Optimasi Kenyamanan Suhu Ruangan Melalui Perancangan Otomatisasi Kipas Angin di Masjid Nurhidayatullah Maguwoharjo - Bagas Rachmadi; Adelia Octora Pristisahida (Syntax Idea, 2031)
This research explores a solution to optimise room temperature comfort in Masjid Nurhidayatullah Maguwoharjo. Mosques are susceptible to temperature and humidity fluctuations, which can affect the worship experience of congregants. To address this challenge, the study developed an automated fan system that dynamically responds to environmental changes, such as temperature and congregation density, using DHT22 temperature and PIR sensors to monitor these parameters. The results indicate that the system effectively maintains temperature and humidity within predefined comfort ranges. Additionally, the study incorporated the TM1637 module and LCD I2C 20x4 display to provide users with temperature, humidity, fan speed, and room capacity information. During testing, temperature and humidity fluctuations throughout the day were recorded, along with changes in congregation density during prayer times. The fan speed adjustment results were reflected in the system's responsiveness to environmental conditions. This research successfully provides an effective solution to enhance comfort in mosques. Therefore, it makes a valuable contribution to the development of automation systems aimed at improving the congregational worship experience and energy efficiency in mosques.